Short–Term Preconditioning With Blood Flow Restricted Exercise Preserves Quadriceps Muscle Endurance in Patients After Anterior Cruciate Ligament Reconstruction - Žargi, Tina; Drobnič, Matej; Stražar, Klemen; Kacin, Alan (Frontiers in Physiology, 2018)
Surgical ACL reconstruction performed with a tourniquet induces compression and ischemic stress of the quadriceps femoris (QF) muscle which can accelerate postoperative weakness. Given that low-load blood flow restricted (BFR) exercise is potent in enhancing muscle oxygenation and vascular function, we hypothesized that short-term preconditioning with low-load BFR exercise can attenuate QF muscle endurance deterioration in the postoperative period. Twenty subjects undergoing arthroscopic ACL reconstruction performed 5 exercise sessions in the last 8 days prior to surgery. They were assigned into either BFR group, performing low-load BFR knee-extension exercise, or SHAM-BFR group, replicating equal training volume with sham occlusion. Blood flow (near-infrared spectroscopy) and surface EMG of QF muscle during sustained isometric contraction at 30% of maximal voluntary isometric contraction (MVIC) torque performed to volitional failure were measured prior to the intervention and again 4 and 12 weeks after surgery. There was an overall decrease (p = 0.033) in MVIC torque over time, however, no significant time-group interaction was found. The time of sustained QF contraction shortened (p=0.002) in SHAM-BFR group by 97±85 s at week 4 and returned to preoperative values at week 12. No change in the time of sustained contraction was detected in BFR group at any time point after surgery. RMS EMG amplitude increased (p=0.009) by 54 ± 58% at week 4 after surgery in BFR group only. BFm increased (p=0.004) by 52 ± 47 % in BFR group, and decreased (p = 0.023) by 32±19 % in SHAM-BFR group at week 4 after surgery. Multivariate regression models of postoperative changes in time of sustained QF contraction revealed its high correlation (R2=0.838; p<0.001) with changes in BFm and RMS EMG in the SHAM-BFR group, whereas no such association was found in the BFR group. In conclusion, enhanced endurance of QF muscle was triggered by combination of augmented muscle fiber recruitment and enhanced muscle perfusion. The latter alludes to a preserving effect of preconditioning with BFR exercise on density and function of QF muscle microcirculation within the first 4 weeks after ACL reconstruction.